Multi-task control strategy for grid-tied inverters based on conservative power theory - Marafão, Fernando P.; Brandão, Danilo I.; Costabeber, Alessando; Paredes, Helmo K.M. (The Institution of Engineering and Technology, 2015)
In recent years, the concept of decentralizing power generation through the deployment of distributed generators (DGs) has been widely accepted and applied, driven by the growing market of renewable energy sources, in particular photovoltaic, wind and small hydro. These distributed generators are normally equipped with a switching power interface (inverter), acting as front end with the grid. In this scenario this paper proposes a multi-task control strategy for distributed generation inverters that simultaneously allows the DG system to inject the available energy, as well as to work as a voltage drop compensator or as an active power filter, mitigating load current disturbances and improving power quality of the grid. The main contribution of the proposed system, with respect to other solutions in the literature, is that the proposed control loops are based on the Conservative Power Theory decompositions. This choice provides decoupled power and current references for the inverter control, offering a very flexible, selective and powerful control strategy for the DG system. The paper also discusses the choice of the current waveform for injecting/absorbing active power into/from the grid, and both sinusoidal and resistive references have been compared in terms of damping capability. Finally, simulation and experimental results are provided in order to validate the proposed functionalities of the DG control system.